2009
DOI: 10.1007/s00415-009-5293-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging supports central pathology in familial dysautonomia

Abstract: Familial dysautonomia (FD) is a hereditary peripheral and central nervous system disorder with poorly defined central neuropathology. This prospective pilot study aimed to determine if MRI would provide objective parameters of central neuropathology. There were 14 study subjects, seven FD individuals (18.6 +/- 4.2 years, 3 female) and seven controls (19.1 +/- 5.8 years, 3 female). All subjects had standardized brain MRI evaluation including quantitative regional volume measurements, diffusion tensor imaging (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…MRI studies showed abnormalities that suggest compromised myelination as well as grey matter and white matter micro-structural damage in FD brains. Abnormal findings are more evident in optic radiation, middle cerebellar pedunculum, and frontal lobe (Axelrod et al , 2010). Significantly, analyses of FD brains showed that the levels of several transcripts and their respective proteins that are involved in myelination are severely reduced in FD brains compared to age-matched healthy individuals (Cheishvili et al , 2007).…”
Section: Clinical Aspects and Pathological Findingsmentioning
confidence: 99%
“…MRI studies showed abnormalities that suggest compromised myelination as well as grey matter and white matter micro-structural damage in FD brains. Abnormal findings are more evident in optic radiation, middle cerebellar pedunculum, and frontal lobe (Axelrod et al , 2010). Significantly, analyses of FD brains showed that the levels of several transcripts and their respective proteins that are involved in myelination are severely reduced in FD brains compared to age-matched healthy individuals (Cheishvili et al , 2007).…”
Section: Clinical Aspects and Pathological Findingsmentioning
confidence: 99%
“…Clinical symptoms involving the CNS include visual impairment (Mendoza-Santiesteban et al, 2012, 2014; Ueki et al, 2016), high anxiety levels, learning impairments (Day, 1979; Sak et al, 1967; Welton et al, 1979; Clayson et al, 1980; Axelrod et al, 2012; Norcliffe-Kaufmann et al, 2016), seizures, decreased motor nerve conduction, deficits in brain stem reflexes (Gutiérrez et al, 2015) and abnormal electroencephalogram (EEG) activity (Niedermeyer et al, 1967; Ochoa, 2003). Neuroimaging studies [magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI)] demonstrate both white and gray matter microstructural damage in FD brains (Axelrod et al, 2010), and pathological studies have revealed enlarged 4th ventricles associated with atrophy in the medulla (Engel and Aring, 1945; Cohen and Solomon, 1955; Brown et al, 1964). Most patients die due to sudden death during sleep or respiratory failure (Axelrod, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the central neuropathology in FD is poorly defined, recent MRI studies indicate that FD patients have abnormal proportions of white matter, decreased optic radiation, and cerebellar microstructural alterations compared to healthy volunteers [17]. The lack of IKAP also results in reduced size and numbers of dorsal-root ganglion (DRG) and sympathetic ganglion (SG) neurons [13,1820].…”
Section: Introductionmentioning
confidence: 99%